Students’ Interest in Learning English Through Wordwall at The Eight Grade of SMP Negeri 1 Buntulia - Hisasmaria Hisasmaria; Idrus Dama (Universitas Islam Darul Ulum Lamongan, 2025)
This research aims to determine the level of the students’ interest in learning English through Wordwall at the eight grade of SMP Negeri 1 Buntulia. The research used mixed methods (Qual-Quan) to identify students’ interest. The data were obtained through questionnaire to determine the level of students’ interest in learning English through Wordwall. The sample of research was 20 students as respondent. Based on the results of the research, researcher found that the level of students’ learning interest through Wordwall media was on Good level with the following details: 19 (95%) students got “Good” category, 1 (5%) students got “Fair” category.